2014
DOI: 10.1039/c4sc00700j
|View full text |Cite
|
Sign up to set email alerts
|

Practical synthesis of water-soluble organic nanoparticles with a single reactive group and a functional carrier scaffold

Abstract: A practical synthesis of biocompatible organic nanoparticles with a reactive group and a functional carrier scaffold was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 48 publications
1
80
0
Order By: Relevance
“…166 The method involved the ring-opening metathesis polymerization of a norbornene dicarboxyimide monomer carrying an activated ester group (N-hydroxy succinimide ester) using Grubbs third-generation catalyst. The activated ester groups of the ROMP-derived polymer were then grafted with tris-(allyloxymethyl)aminomethane to produce a large number of terminal olefin groups across the polymer chain.…”
Section: Nitrene Insertion/couplingmentioning
confidence: 99%
“…166 The method involved the ring-opening metathesis polymerization of a norbornene dicarboxyimide monomer carrying an activated ester group (N-hydroxy succinimide ester) using Grubbs third-generation catalyst. The activated ester groups of the ROMP-derived polymer were then grafted with tris-(allyloxymethyl)aminomethane to produce a large number of terminal olefin groups across the polymer chain.…”
Section: Nitrene Insertion/couplingmentioning
confidence: 99%
“…For example, a ring closing metathesis (RCM) reaction was used as the driving force for the collapse of single polymer chain. 94 …”
Section: Single-chain Polymeric Nanoparticles (Scnps)mentioning
confidence: 99%
“…They are synthesized, generally at high dilution (∼ 1 mg/mL), through purely intramolecular cross-linking of the reactive functional groups of single polymer precursors. A growing interest is being devoted in recent years to develop a SCNPbased technology with multiple applications in catalysis [6][7][8][9] , nanomedicine 10,11 , bioimaging 12,13 , biosensing 14 , or rheology [15][16][17] among others. A recent review of the state-of-the-art in fundamentals and applications of SCNPs can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%